Correct treatment of rotation of sliding surfaces in a kinematic model of the triple friction pendulum bearing. (7th May 2012) - Becker, Tracy C.; Mahin, Stephen A.
ABSTRACT This paper addresses the treatment of the rotation of the internal components of the triple friction pendulum (TFP) isolation bearing in a numerical model previously presented by the authors. The numerical model is based on the kinematic behavior of the individual sliding surfaces and the constitutive relationships between them. The modification suggested in this paper improves the performance of the model so that the results exactly match that of the one‐dimensional piecewise linear behavior previously derived for the TFP bearing for restricted properties. The improved numerical model simulates bidirectional shear response and places no a priori restrictions on the bearing properties. The modification is put in the form of a technical communication so that the notation used and the basis of the correction could be presented with adequate clarity and so that an example of the benefit of the correction could be presented. Copyright © 2012 John Wiley & Sons, Ltd.